Pengembangan Media Pembelajaran Berbasis Video pada Mata Pelajaran Pemograman Dasar di Sekolah Menengah Kejuruan - Sari, Yosi Nofita; Ridhani, Deviana; Dewi, Afriola (Universitas Negeri Padang, 2022)
Learning media is a way of delivering messages or information to students during the teaching and learning process in order to pique their interest in learning. There is a demand for video-based learning media, and learning media may be developed using Basic Programming learning resources. The goal of this research is to provide video-based learning medium for Basic Programming classes in vocational high schools. This is a research and development (R&D) project that uses a four-dimensional model (define, design, develop and disseminate). T category, often known as a practical medium to which the instructor replied, received a score of 0.93. The teacher's answer has a practicality of 0.85, and it may be employed successfully with the post-test findings, as evidenced by the students' classical completeness of 0.81 in the high category.